DESIGN OF EMPLOYEE PERFORMANCE APPRAISAL USING THE GRAPHIC RATING SCALE METHOD IN LEARNING RESOURCES AND LIBRARIES AT PGRI ADI BUANA UNIVERSITY - Hariawan, Ferry; Harwanto, Harwanto; Adi, Kharisma (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
In the world of work, employee performance appraisal has an important role. This is related to decisions to be taken by the leadership, regarding the performance of their employees. From the preliminary research at the Learning Resources and Libraries of the PGRI Adi Buana University Surabaya, it turns out that it does not have an employee performance appraisal system. After conducting interviews and observations by studying the library operational cycle, this study focused on the design of employee performance appraisals using the Graphic Rating Scale Method by separating several elements of the appraiser to be compared with one another. The purpose of this research is to determine the performance of each employee so that it makes it easier for leaders to provide training, mentoring and supervision in the management of Human Resources (HR) at Learning Resources and Libraries PGRI Adi Buana University Surabaya. This research is a field research, which is a research carried out systematically by raising existing data in the field. The research method used in this research is to use descriptive qualitative research methods. The results showed that the performance appraisal design that will be made has gone through the process of gathering information through interviews and Focus Group Discussion (FGD). The rating scale used in the Graphic Rating Scale Method is the Likert scale with the same 5-point interval scale. There are 8 (eight) statements to be filled in and made using the online google form.